2015
DOI: 10.14411/fp.2015.024
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Ligophorus uruguayense and L. saladensis (Monogenea: Ancyrocephalidae) from Mugil liza (Teleostei: Mugilidae) in southern Brazil

Abstract: Representatives of Ligophorus Euzet et Suriano, 1977 were found on the gills of Mugil liza Valenciennes caught in southern Brazil. They were identified as Ligophorus uruguayense Failla Siquier et Ostrowski de Núñez, 2009 and Ligophorus saladensis Marcotegui et Martorelli, 2009, even though specific identification proved to be difficult due to inconsistencies in some diagnostic features reported for these two species. Therefore, a combined morphological and molecular approach was used to critically review the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
(32 reference statements)
0
22
0
2
Order By: Relevance
“…Parasite identification was performed using the morphology and size of sclerotized parts of the attachment apparatus (haptor) and that of the genitalia (vagina and male copulatory organs) following the original description of Birgi and Euzet [ 23 ]. While some individuals were fixed and mounted in a mixture of glycerin and ammonium picrate [ 48 ] for further morphological study, three adult specimens (fixed alive together with the host and preserved in alcohol) were prepared for PCR amplification following the protocol of Marchiori et al [ 49 ], i.e., directly without DNA extraction. Standard PCR was performed with two primers specific to the D1-D2 domain of the large subunit region (LSU) of the 28S ribosomal gene: C1 (forward; 5’-ACCCGCTGAATTTAAGCAT-3’) and D2 (reverse; 5’-TGGTCCGTGTTTCAAGAC-3’) [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Parasite identification was performed using the morphology and size of sclerotized parts of the attachment apparatus (haptor) and that of the genitalia (vagina and male copulatory organs) following the original description of Birgi and Euzet [ 23 ]. While some individuals were fixed and mounted in a mixture of glycerin and ammonium picrate [ 48 ] for further morphological study, three adult specimens (fixed alive together with the host and preserved in alcohol) were prepared for PCR amplification following the protocol of Marchiori et al [ 49 ], i.e., directly without DNA extraction. Standard PCR was performed with two primers specific to the D1-D2 domain of the large subunit region (LSU) of the 28S ribosomal gene: C1 (forward; 5’-ACCCGCTGAATTTAAGCAT-3’) and D2 (reverse; 5’-TGGTCCGTGTTTCAAGAC-3’) [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…of Ligophorus due to the small size of the main diagnostic structures associated with the genus and their close resemblance under an optical microscope (Sarabeev et al 2005). Nevertheless, Marchiori et al (2015) have confirmed the validity of two closely related species, L. uruguayense and L. saladensis, through a combined morphological and molecular approach.…”
Section: Species Of Ligophorusmentioning
confidence: 86%
“…Several 95% ethanol-fixed specimens were processed for confocal laser scanning microscopy following standard procedures [ 17 18 ], using a Leica TCS SP2 confocal microscope equipped with an inverted Leica DMIRE2 microscope and a PL APO 363 oil immersion objective (numerical aperture 5 1.4, z section setting minimum 200) at the Live Cell Imaging Center, Department of Biology, University of Rostock.…”
Section: Methodsmentioning
confidence: 99%